Heterodyne Interferometry Applied to the Characterization of Acousto-Electro-Optic Light Modulators - Kitano, C. [UNESP]; Higuti, R. T. [UNESP]; Sakamoto, J. M. S.; Pacheco, G. M. (American Institute of Physics (AIP), 2012)
When the electro-optic and acousto-optic effects are combined into a single device, the resulting acousto-electro-optic (AEO) modulator shows improved flexibility to overcome some limitations of the individual modulators or their cascade combinations. By using optical interferometry, it is possible to investigate the AEO modulator behavior as a function of this applied voltage. By this way, a lithium niobate AEO modulator is positioned in one of the arms of a Mach-Zehnder interferometer and operates at 62 MHz frequency, which constitutes the intermediate frequency of the heterodyne interferometer. Operating the AEO modulator in the acousto-optic small diffraction efficiency regime, the photodetected signal amplitude and phase are analyzed, and the induced phase shift, transmission curve and linearity response are obtained. The experimental results show good agreement with that expected from the coupled-mode theory. The possibility of linear control of the optical phase shift by the external voltage, from 0 to 2 p radians, is demonstrated.
Keywords: Interferometers; Acousto-optical devices; Electro-optical effects